2004
DOI: 10.4049/jimmunol.173.9.5626
|View full text |Cite
|
Sign up to set email alerts
|

The IL-27 Receptor (WSX-1) Is an Inhibitor of Innate and Adaptive Elements of Type 2 Immunity

Abstract: Although previous studies have investigated the role of IL-27/WSX-1 interactions in the regulation of Th1 responses, little is known about their role in regulating Th2-type responses. Studies presented in this work identify a direct role for IL-27/WSX-1 interactions in the negative regulation of type 2 responses independent of effects on type 1 cytokines. WSX-1−/− mice infected with the gastrointestinal helminth Trichuris muris displayed accelerated expulsion of parasites and the development of exaggerated gob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
211
1
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 223 publications
(229 citation statements)
references
References 46 publications
15
211
1
2
Order By: Relevance
“…A similar phenotype has been shown when IL-27Ra À/À (WSX-1 À/À ) mice were infected with T. muris [36]. These mice developed a strong overproliferative Th2 response, which led to accelerated worm expulsion before day 14 p.i [36]. Recent work has highlighted a role for IL-27 in the suppression of Th2 development of naïve T cells and Th2 cytokine production by polarized Th2 cells by upregulating the expression of the Th1 transcription factor T-bet and simultaneously downregulating GATA3, essential for the Th2 response [37,38].…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…A similar phenotype has been shown when IL-27Ra À/À (WSX-1 À/À ) mice were infected with T. muris [36]. These mice developed a strong overproliferative Th2 response, which led to accelerated worm expulsion before day 14 p.i [36]. Recent work has highlighted a role for IL-27 in the suppression of Th2 development of naïve T cells and Th2 cytokine production by polarized Th2 cells by upregulating the expression of the Th1 transcription factor T-bet and simultaneously downregulating GATA3, essential for the Th2 response [37,38].…”
Section: Discussionsupporting
confidence: 73%
“…revealed exaggerated goblet cell and epithelial cell hyperplasia. Again, this phenotype mimics the changes observed in WSX-1 À/À mice [36]. Moreover, T. muris infection of IL-10 À/À gp130 fl/fl CD4-Cre 1 mice caused an influx of macrophages and neutrophils at day 14 p.i., which was in agreement with the augmented inflammation seen in the caecum and with the production of proinflammatory cytokines.…”
supporting
confidence: 71%
See 1 more Smart Citation
“…To this end, NOD/SCIDIl2rg À/À (NSG) mice were injected with B-ALL cells obtained from BM pediatric patients and treated with IL-27 or phosphate buffered saline (PBS). On the basis of previous studies, 17 TICs were identified as CD133 þ CD19 À cells, as this population (1) was the only one within the whole B-ALL tumor that could self-renew to engraft serial SCID/NOD recipients, 17 (2) differentiates in vivo to produce leukemias with similar immunophenotypic and karyotypic features similar to those detected in primary tumor samples 17 and (3) was more resistant to treatment with dexamethasone and vincristine, 17 key components in childhood ALL therapy, than the bulk leukemia population.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6] The IL-27R contains the unique receptor subunit WSX-1, paired with the gp130 chain; both chains are necessary for IL-27 signaling. 7,8 IL-27 exerts antitumor activity in different tumors through indirect 5,9-11 and direct mechanisms.…”
Section: Introductionmentioning
confidence: 99%